Colloidal processing of low-concentrated zirconia nanosuspension using osmotic consolidation. Issue 10 (1st August 2016) - Trunec, Martin; Pouchly, Vaclav
Abstract: Colloidal processing was applied to a water-based suspension with 5 vol% zirconia nanoparticles of 10–15 nm in size. The nanosuspension was concentrated by evaporation or by a newly developed method of osmotic dehydration. The viscosity and stability of concentrated nanosuspensions were investigated. Osmotic consolidation of both nanosuspensions, concentrated by evaporation and osmotically dehydrated, was performed in a solution of polyethylene oxide separated from the nanosuspensions using a permeable membrane. Osmotic pressure generated a water flow from the nanosuspension to the polymer solution, concentrating the nanosuspension and eventually consolidating the nanoparticle network. The pore size distribution in dried nanoparticle compacts and pore size evolution during sintering were evaluated and discussed. The nanozirconia compacts were densified by pressure-less sintering to a relative density of up to 99.7% while maintaining the nanocrystalline structure.